Upper mesospheric lunar tides over middle and high latitudes during sudden stratospheric warming events. Issue 4 (15th April 2015) - Chau, J. L.; Hoffmann, P.; Pedatella, N. M.; Matthias, V.; Stober, G.
Abstract In recent years there have been a series of reported ground‐ and satellite‐based observations of lunar tide signatures in the equatorial and low latitude ionosphere/thermosphere around sudden stratospheric warming (SSW) events. This lower atmosphere/ionosphere coupling has been suggested to be via the E region dynamo. In this work we present the results of analyzing 6 years of hourly upper mesospheric winds from specular meteor radars over a midlatitude (54°N) station and a high latitude (69°N) station. Instead of correlating our results with typical definitions of SSWs, we use the definition of polar vortex weaking (PVW) used by Zhang and Forbes (2014). This definition provides a better representation of the strength in middle atmospheric dynamics that should be responsible for the waves propagating to the E region. We have performed a wave decomposition on hourly wind data in 21 day segments, shifted by 1 day. In addition to the radar wind data, the analysis has been applied to simulations from Whole Atmosphere Community Climate Model Extended version and the thermosphere‐ionosphere‐mesosphere electrodynamics general circulation model. Our results indicate that the semidiurnal lunar tide (M2) enhances in northern hemispheric winter months, over both middle and high latitudes. The time and magnitude of M2 are highly correlated with the time and associated zonal wind of PVW. At middle/high latitudes, M2 in the upper mesosphere occurs after/before the PVW. At both latitudes, the maximum amplitude of M2 is directly proportional to the strength of PVW westward wind. We have found that M2 amplitudes could be comparable to semidiurnal solar tide amplitudes, particularly around PVW and equinoxes. Besides these general results, we have also found peculiarities in some events, particularly at high latitudes. These peculiarities point to the need of considering the longitudinal features of the polar stratosphere and the upper mesosphere and lower thermosphere regions. For example, during SSW 2009, we found that M2 enhances many days before PVW which is not in agreement with most of our results.